2011
DOI: 10.1016/j.fct.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of promoting effect of titanium dioxide particles on ultraviolet B-initiated skin carcinogenesis in rats

Abstract: Titanium dioxide (TiO(2)) is used in sunscreens and cosmetics as an ultraviolet light screen. TiO(2) has carcinogenic activity in the rat lung, but its effect on the skin has not been reported. We examined the promoting/carcinogenic effect of nano-size TiO(2) particles using a two-stage skin model. c-Ha-ras proto-oncogene transgenic (Hras128) rats, which are sensitive to skin carcinogenesis, and their wild-type siblings were exposed to ultraviolet B radiation on shaved back skin twice weekly for 10 weeks; then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…the epidermis and reach the underlying tissue (Xu et al, 2011). This speculation is consistent with a report by Newman et al (2009) demonstrating an absence of penetration of TiO 2 through the epidermis and hair follicles (Newman et al, 2009).…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…the epidermis and reach the underlying tissue (Xu et al, 2011). This speculation is consistent with a report by Newman et al (2009) demonstrating an absence of penetration of TiO 2 through the epidermis and hair follicles (Newman et al, 2009).…”
Section: Introductionsupporting
confidence: 80%
“…Thus, the lack of skin promotion/carcinogenesis effects is probably due to lack of penetration of the particles through the epidermis to the dermis where cytogenetic cells of skin carcinogenesis reside. In another study, we found no promoting effect of TiO 2 particles in a UVB-initiated long-term (52 weeks) skin carcinogenesis study and no penetration of TiO 2 particles through the epidermis (Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations